Climate and habitat configuration limit range expansion and patterns of dispersal in a non‐native lizard. Issue 7 (22nd February 2021) - Williams, Robert J.; Dunn, Alison M.; Mendes da Costa, Lily; Hassall, Christopher
Abstract: Invasive species are one of the main causes of biodiversity loss worldwide. As introduced, populations increase in abundance and geographical range, so does the potential for negative impacts on native communities. As such, there is a need to better understand the processes driving range expansion as species become established in recipient landscapes. Through an investigation into capacity for population growth and range expansion of introduced populations of a non‐native lizard ( Podarcis muralis ), we aimed to demonstrate how multi‐scale factors influence spatial spread, population growth, and invasion potential in introduced species. We collated location records of P. muralis presence in England, UK through data collected from field surveys and a citizen science campaign. We used these data as input for presence‐background models to predict areas of climate suitability at a national‐scale (5 km resolution), and fine‐scale habitat suitability at the local scale (2 m resolution). We then integrated local models into an individual‐based modeling platform to simulate population dynamics and forecast range expansion for 10 populations in heterogeneous landscapes. National‐scale models indicated climate suitability has restricted the species to the southern parts of the UK, primarily by a latitudinal cline in overwintering conditions. Patterns of population growth and range expansion were related to differences in local landscape configuration and heterogeneity. Growth curves suggest populations could be in the early stages of exponential growth. However, annual rates of range expansion are predicted to be low (5–16 m). We conclude that extensive nationwide range expansion through secondary introduction is likely to be restricted by currently unsuitable climate beyond southern regions of the UK. However, exponential growth of local populations in habitats providing transport pathways is likely to increase opportunities for regional expansion. The broad habitat niche of P. muralis, coupled with configuration of habitat patches in the landscape, allows populations to increase locally with minimal dispersal. Abstract : We investigated the potential for population growth and range expansion of introduced populations of a non‐native lizard ( Podarcis muralis ), considering multi‐scale factors influencing growth, and spatial spread. National‐scale models indicated climate suitability restricted to the southern parts of the UK, limited by a latitudinal cline in overwintering conditions. Patterns of local population growth and range expansion were related to differences in local landscape configuration and heterogeneity. The broad habitat niche of P. muralis, coupled with configuration of habitat patches in the landscape, allows populations to increase locally with minimal dispersal